Distribution of Neohelice granulata (Dana 1851) in its northernmost latitudinal occurrence in a tropical mangrove forest, Brazil (Crustacea, Decapoda, Brachyura, Grapsoidea, Varunidae). - Gregati, Rafael Augusto; Negreiros-Fransozo, Maria Lucia (My University, 2008)
Neohelice granulata ecological distribution was evaluated in its northernmost latitudinal occurrence in a Brazilian tropical mangrove (23[degree]13'4" S, 44[degree]42'47" W). Samples were collected in three sites along the main river in the mangrove. Crabs were manually captured by two people, 15 min each, at low tide periods. The sex of the animals was assessed and carapace width measured. The size-frequency distribution was determined in each site. Environmental factors (salinity, temperature, organic matter and sediment texture) were analyzed, compared among sites and related to crab abundance and size in each site. Crab abundance decreased with the distance from the sea. Juvenile crabs were more frequent next to the sea, whereas larger and ovigerous ones were mainly found in the most distant site. Crab size was proportional to the organic matter percentage in the sediment. N. granulata spatial distribution varies along the river course, which is probably related to the most productive areas that have more nutrients available; this may also occur in order to prevent intraspecific competition.